Edukasi Penerapan Aplikasi PRIMAKU terhadap Pertumbuhan Bayi Usia 6-12 Bulan di PKM Bajeng - Sutrani Syarif; Rika Rahmawati; Nursaidah Nursaidah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Posyandu is expected to be able to detect any deviations in growth and development early and provide recommendations to immediately visit related health services. Stimulation recommendations are also given if the detection results show that there is dysfunction in growth and development, so that the dysfunction does not experience more severe disorders. Delays in growth and development in children that are detected early are very important and are part of the duties of posyandu cadres. There are several applications that can be accessed by the community at home, such as the "Nutritional Status Check", "Nutrition Calculator", and "PRIMAKU" applications, where these applications can be downloaded using a smartphone on the Google Playstore, these applications can be used to help parents monitor their children's growth and development while at home. 5 The Ministry of Health has launched the book Stimulation, Detection and Early Intervention of Growth and Development (SDIDTK) (Karima et al., 2021; N et al., 2019).